The achievements and experiences of poverty alleviation in rural China - Liu, Jian (International Food Policy Research Institute, 2005)
In its pursuit of poverty alleviation and development, China has charted its own path, suitable for its own conditions. This path involves government leadership, social participation, self-reliance, an orientation toward economic development, and an integrated development approach... Although China has made enormous progress in poverty alleviation and development, it still faces many problems. To address these problems, the Chinese government will increase support for poverty-stricken regions and impoverished people and continually improve the mechanisms of poverty alleviation according to its pace of economic and social development. It will also pay attention to needy groups that emerge from economic structural adjustment and will promote the capacity for sustainable development among poor people and regions through investments in infrastructure and human capital.